Identification of clusters of asthma control: A preliminary analysis of the inspirers studies - Jácome, Cristina (2021)
This work was funded by ERDF (European Regional Development Fund) through the operations: POCI- -01-0145-FEDER-029130 (“mINSPIRERS—mHealth to measure and improve adherence to medication in chronic obstructive respiratory diseases - generalisation and evaluation of gamification, peer support and advanced image processing technologies”) co-funded by the COMPETE2020 (Programa Operacional Competitividade e Internacionalização), Portugal 2020 and by Portuguese Funds through FCT (Fundação para a Ciência e a Tecnologia).